Assessment of Indigenous and Crossbred Cattle Bull’s SeminalCharacteristics - Vorikollu, Sai krishna; Singh, Lakavath Ram; Ramana, Kudikilla Venkata; Reddy, Kankanalapally Jagan Mohan (The Indian Journal of Animal Reproduction, 2024)
The present investigation on cattle bull semen was undertaken at Frozen Semen Bull Station, Karimnagar, Telangana. The study was carried out on four types of cattle breeds (3 to 5 years of age) viz., Gir, Ongole, Jersey and CBJY (Cross bred Jersey). Semen was collected using artificial vagina method twice weekly from each of the bulls and a total of 32 ejaculates were studied. The semen was diluted with Egg Yolk Tris Citrate (EYTC) extender and was evaluated for physical characteristics of neat semen, Motility parameters and sperm viability percentage. The investigation revealed that Gir bull semen has significantly (p<0.05) higher ejaculate Volume, Mass motility, Individual motility, sperm concentration compared to other breeds under this study. Whereas, Jersey bull semen has significantly higher sperm viability percentage.